2014
DOI: 10.1152/physrev.00030.2013
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Regulation of Metabolism

Abstract: Thyroid hormone (TH) is required for normal development as well as regulating metabolism in the adult. The thyroid hormone receptor (TR) isoforms, α and β, are differentially expressed in tissues and have distinct roles in TH signaling. Local activation of thyroxine (T4), to the active form, triiodothyronine (T3), by 5'-deiodinase type 2 (D2) is a key mechanism of TH regulation of metabolism. D2 is expressed in the hypothalamus, white fat, brown adipose tissue (BAT), and skeletal muscle and is required for ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
1,299
4
33

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,732 publications
(1,442 citation statements)
references
References 267 publications
18
1,299
4
33
Order By: Relevance
“…T3 is known to signal within the hypothalamus and is essential as a mediator for environmental regulators of growth and energy balance (Mullur et al, 2014). However, the genes on which T3 directly acts upon to bring about these changes in the hypothalamus are poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…T3 is known to signal within the hypothalamus and is essential as a mediator for environmental regulators of growth and energy balance (Mullur et al, 2014). However, the genes on which T3 directly acts upon to bring about these changes in the hypothalamus are poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…TRα1 and TRβ1 are the two main thyroid hormone-binding isoforms and regulate transcription either by direct binding to thyroid hormone response elements (TREs) in target genes or by modulating the activity of other transcription factors and signaling pathways (21,22). TRβ mediates the majority of the actions of T3 in the liver (23), playing an important role in regulating metabolism (24,25), regeneration (26), senescence (27), and carcinogenesis (28). Recent findings suggest that nonalcoholic fatty liver disease, which can progress to liver fibrosis, cirrhosis, and hepatocellular carcinoma, is associated with impaired thyroid action in the liver (29)(30)(31)(32).…”
mentioning
confidence: 99%
“…TH has important roles in regulating hepatic fatty acid, cholesterol, and carbohydrate homeostasis (6,7). Indeed, recent metabolomics analyses showed that acute TH treatment increased acylcarnitines in the mouse liver (8).…”
Section: Introductionmentioning
confidence: 99%